2020
DOI: 10.3802/jgo.2020.31.e17
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and survival of ovarian cancer patients treated with neoadjuvant chemotherapy but not undergoing interval debulking surgery

Abstract: Objective: Neoadjuvant chemotherapy (NACT) followed by interval debulking surgery (IDS) confers similar outcomes as primary debulking surgery and chemotherapy. Little is known about patients who receive NACT but do not undergo debulking surgery. Our aim was to characterize these patients. Methods: We prospectively identified patients with newly diagnosed stage III/IV ovarian cancer treated with NACT from 7/1/15-12/1/17. Fisher exact and Wilcoxon rank-sum tests were used to compare clinical characteristics by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Real-life reports indicate that more than a quarter of women with advanced ovarian cancer who are treated with neoadjuvant chemotherapy do not ever reach the point of being able to undergo cytoreductive surgery at an interval setting. 5 Even though cytoreductive surgery is the gold standard of national and international guidelines, in actual practice a considerable proportion of patients with advanced ovarian cancer will not have any surgery at all as part of their initial management. 1 The UK National Cancer Data Repository reports that around 40% of patients with newly diagnosed advanced ovarian cancer have never undergone debulking surgery of any timing, with up to 25% receiving palliative care alone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Real-life reports indicate that more than a quarter of women with advanced ovarian cancer who are treated with neoadjuvant chemotherapy do not ever reach the point of being able to undergo cytoreductive surgery at an interval setting. 5 Even though cytoreductive surgery is the gold standard of national and international guidelines, in actual practice a considerable proportion of patients with advanced ovarian cancer will not have any surgery at all as part of their initial management. 1 The UK National Cancer Data Repository reports that around 40% of patients with newly diagnosed advanced ovarian cancer have never undergone debulking surgery of any timing, with up to 25% receiving palliative care alone.…”
mentioning
confidence: 99%
“…As per our intuitive expectation, it has been shown that patients who never underwent surgery had a more than threefold increase in all-cause mortality compared with those who underwent surgery at some point in their disease journey, even after risk adjustment for age, tumor dissemination patterns, and dose reductions. 5 Hence, our focus as gynecological oncology experts for now is not just to have endless debates and hypotheses about the timing of surgery in advanced disease; the prospectively randomized phase III international TRUST trial (AGO-OVAR-OP.7/NCT02828618) has Editorial been perfectly designed to answer this in appropriately specialized settings with adequate experience in radical debulkings despite the high tumor load. 6 Our goal should be to direct patients with advanced disease to expert dedicated centers that will be able to adequately treat them, despite their high tumor load, and the challenges arising from that.…”
mentioning
confidence: 99%
“…In this issue by Liu et al [8], the team from Memorial Sloan Kettering Cancer Center has demonstrated that more than a quarter of women with advanced EOC who are treated with neoadjuvant chemotherapy (NACT) do not ever reach the point of being able to undergo cytoreductive surgery at an interval setting (IDS). Advanced age, lower albumin levels, frailty scores and extensive disease of predominantly high-grade serous histology, were identified as the most significant risk factors for inability to undergo surgery.…”
mentioning
confidence: 99%
“…Advanced age, lower albumin levels, frailty scores and extensive disease of predominantly high-grade serous histology, were identified as the most significant risk factors for inability to undergo surgery. The reasons of that were mainly quoted as 1) extent of disease not amenable to surgery or lack of response to NACT; 2) patient comorbidities preventing surgery; 3) both extent of disease and patient comorbidity [8]. The findings of this study confirmed the intuitive expectation that these, never operated, patients will have a >3-fold increase in all-cause mortality compared to those who underwent surgery at some point in their journey, even after risk adjustment for age, tumor dissemination patterns and dose reductions.…”
mentioning
confidence: 99%
See 1 more Smart Citation